The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acsami.8b08803
|View full text |Cite
|
Sign up to set email alerts
|

Control of Crystallinity in PbPc:C60 Blend Film and Application for Inverted Near-Infrared Organic Photodetector

Abstract: Inverted near-infrared (NIR) organic photodetectors (OPDs) are required to combine the OPDs with an n-channel silicon-based integrated circuit. NIR absorption in the 930-960 nm range is important because the intensity of solar irradiation is low in this wavelength regime. Here, we controlled the crystallinity of lead(II) phthalocyanine (PbPc) in a PbPc:C blend film to obtain NIR absorption. To form a triclinic phase responsible for NIR light absorption, a substrate was heated during fabrication and C was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 48 publications
0
23
1
Order By: Relevance
“…It can be found that both the planar heterojunction and mixed active layers show two absorption bands at 730 and 900 nm in the NIR region, which can be assigned to the monoclinic and triclinic phase absorptions of PbPc, respectively. [15][16][17][18][19] The PbPc (60 nm)/C 60 (40 nm) planar heterojunction layer displays the highest triclinic phase absorption, while a lower ones for the PbPc (20 nm)/PbPc:C 60 (80 nm) mixed active layers, which is attributed to the decreased component of PbPc in the mixed active films. This trend is reverse to the EQE spectra of the devices shown in Figure 2, where the device with a 1:1 mixed active layer appears the highest response at the triclinic phase absorption region.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It can be found that both the planar heterojunction and mixed active layers show two absorption bands at 730 and 900 nm in the NIR region, which can be assigned to the monoclinic and triclinic phase absorptions of PbPc, respectively. [15][16][17][18][19] The PbPc (60 nm)/C 60 (40 nm) planar heterojunction layer displays the highest triclinic phase absorption, while a lower ones for the PbPc (20 nm)/PbPc:C 60 (80 nm) mixed active layers, which is attributed to the decreased component of PbPc in the mixed active films. This trend is reverse to the EQE spectra of the devices shown in Figure 2, where the device with a 1:1 mixed active layer appears the highest response at the triclinic phase absorption region.…”
Section: Resultsmentioning
confidence: 96%
“…Among these compounds, lead phthalocyanine (PbPc) has been used for NIR photovoltaic devices owing to its small bandgap with an absorption band extended to about 1000 nm as well as a high extinct coefficient. [15][16][17] In this study, photomultiplication type NIR-OPDs are demonstrated both in PbPc/C 60 heterojunction and PbPc: C 60 mixed active layer devices. Compared with the planar heterojunction device, the mixed active layer devices exhibits a higher NIR response.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, triclinic crystal structures are desirable to enhance the optical sensitivity in the NIR regime for PbPc‐based OPDs. In 2018, Choi et al demonstrated an effective method to control the crystallinity of PbPc in blend films, where the substrate was heated in the process of preparation and C 60 served as both templating layer and electron extraction layer . X‐ray diffraction measurements confirmed the dramatic changes to the film's crystal structure.…”
Section: Nir Photoelectric Materials For Opdsmentioning
confidence: 99%
“…B, The specific detectivity spectra for the devices fabricated by different processing conditions. Source : Reproduced with permission from Reference Copyright 2018, American Chemical Society…”
Section: Nir Photoelectric Materials For Opdsmentioning
confidence: 99%
“…For example, Su et al fabricated an OPD device with PbPc:C 70 blend as the active layer exhibiting broad-band response in the wavelength range of 300-1100 nm and the EQE of ≈30.2% in the NIR region (at a wavelength of 890 nm). [3] Meanwhile, Choi et al developed a PbPc-based inverted OPD device demonstrating the dark current density of ≈10 −6 A cm −2 and EQE of 31.1% at a wavelength of 970 nm, and 244 mA W −1 and 1.36 × 10 11 cm Hz 1/2 W −1 for a respective parameter of responsivity and specific detectivity measured at a bias voltage of −3 V. [28] Another Pc-derivative material, ClAlPc, also shows strong optical absorption in the NIR region with a narrow-band covering from 650 to 750 nm as compared to that of other Pc materials, such as PbPc, zinc phthalocyanine, and tin naphthalocyanine. [4,17,25,29,30] Joo et al has demonstrated another Pc-based NIR absorber, chloroindium phthalocyanine (ClInPc) blended with C 60 as the active layer, which achieved a dark current density of ≈10 −8 A cm −2 , EQE > 80% (at a wavelength of ≈705 nm), specific detectivity of 4.5 × 10 12 Jones, LDR of 77.2 dB, and frequency response of 2.85 kHz.…”
Section: Introductionmentioning
confidence: 99%